Anatomical and Morphological Features of Scots Pine Heartwood Formation in Two Forest Types in the Middle Taiga Subzone - Tatiana V. Tarelkina; Natalia A. Galibina; Sergei A. Moshnikov; Kseniya M. Nikerova; Elena V. Moshkina; Nadezhda V. Genikova (Forests, 2022)
Currently, there is no consensus on how growing conditions affect the heartwood formation in Scots pine. Comparing the results obtained by different authors is difficult due to methodology differences and poor descriptions of the objects used. We selected two sample plots in (1) a blueberry pine forest on nutrient-rich and moist soil and (2) a lichen pine forest on nutrient-poor and dry soil and performed their detailed characterization. The sample plots were located 22 km apart in the middle taiga subzone (Karelia Republic, northwest Russia). In each sample plot, we selected five dominant trees (model trees), from which we took cores at different trunk heights (0.3, 1.5, 4.5, 7.5 and 10.5 m). The cores were treated with 2,6-dichlorophenolindophenol to identify the heartwood zone. Additionally, samples were taken to study the structural features of the transition zone between sapwood and heartwood. In both forest types, the number of heartwood rings depended on the cambium age, and the patterns of parenchyma cell death did not differ in the transition zone. These facts point to a predominantly internal regulation of the heartwood formation in Scots pine. The heartwood radius and its proportion on the cross-sections were significantly higher in the blueberry pine forest than in the lichen pine forest, despite the relative values of the annual ring width. Further research is needed to develop successful Scots pine heartwood width models under a wide range of conditions.